Pengaruh keahlian forensik, skeptisme profesional, dan tekanan anggaran waktu terhadap kemampuan auditor dalam mendeteksi kecurangan (fraud) - Budiantoro, Harry; Fajriyah, Nurul; Lapae, Kanaya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of forensic expertise, professional skepticism, and time budget pressure on the ability of auditors to detect fraud (Fraud) partially or simultaneously. The research method used is quantitative research methods and uses primary data that is the Public Accounting Firm (KAP) in the Central Jakarta Region. The sample used as many as 10 public accounting firms (KAP) through the convenience sampling method. The analytical method used is multiple linear regression sing SPSS application version 25. The results of this study indicate simultaneously the variables of Forensic Expertise, Professional Skeptism, and Time Budget Pressure have a significant effect on Auditor's Ability to Detect Fraud (fraud). Furthermore, the variable of forensic expertise and professional skepticism partially has a positive effect on the ability of auditors to detect fraud, and the variable time budget pressure does not affect the ability of auditors to detect fraud.